In deadly fashion - Simpson, Rosemary, 1942- (Simpson, Rosemary, 1942- Gilded Age mystery., 2025)
"AUGUST 1891: Prudence has her heart set on wearing her mother's wedding gown on the happy day, but she soon discovers the material has deteriorated so badly that it cannot be refurbished. With time running out, she decides to seek out a new American designer, a woman who trained in the House of Worth, the makers of the original dress in Paris, who now has a shop in New York City. The gown is nearly complete when the expert seamstress overseeing the project is found dead in the studio, with Prudence's wedding dress slashed to ribbons and scattered over the body. The murder incites a scandal, as client after client deserts the now struggling designer. Now not only must Prudence find the murderer, she must rescue the talented young couturière's reputation--all while another gown is being hastily sewn. The police suspect the seamstress's disgruntled lover. Prudence wonders about other designers competing in the cutthroat world of high fashion. But when additional wedding plans start to go awry, it's clear there is an elaborate campaign of sabotage and that either Prudence or Geoffrey or both are being targeted. Once again they must work as a team to expose whoever is determined to ruin their lives--before the future they've so long dreamed of is left in tatters..."--Amazon.